0249 Night Sleep And Napping Together Consolidate Infants' Motor Problem Solving. (12th April 2019) - Horger, Melissa N; Berger, Sarah E; DeMasi, Aaron; Allia, Angelina M; Scher, Anat
Abstract: Introduction: In adults, napping and night sleep have an additive effect on motor learning (Korman et al., 2007). Infant research typically tests the impact of either napping or night sleep on learning, but there may be a similar cumulative pattern (Seehagen et al., 2015). However, because infant sleep differs from adult sleep in duration, timing, and structure (Ednick et al., 2009), and possibly in functions, we cannot generalize across ages. The current study examines the roles of napping and night sleep on motor problem solving in infancy. Methods: Thirty-two infants, within a week of giving up crawling, stood upright at the entrance of a tunnel. Navigating the tunnel requires a postural shift from walking to crawling, which is taxing for new walkers. A strict 15-step training protocol controlled when and how to highlight relevant details of the task. The session ended once infants exited the tunnel or exhausted the protocol. Infants were tested on this task again, after their nap ( n =9), after a delay without a nap ( n =13), or immediately ( n =10) after training. They also received it the next morning after night sleep. The primary outcome measure for all sessions was the number of prompts. Results: Proportion of change in prompt number from training to test and test to follow-up were calculated. The immediate group showed a 40% improvement from training to test, but a 35% decrement from test to follow-up. The nap group showed a 20% decrement from training to test, but a 47% improvement from test to follow-up. The no nap group showed a 71% decrement from training to test, and a further decrement of 9% from test to follow-up. Conclusion: Surprisingly, the nap group did not improve from training to test; however, they were the only group to improve after night sleep. In contrast, neither of the other groups demonstrated long-term improvements. Thus, it appears that napping and night sleep have an additive effect. Support (If Any): This work was supported by National Science Foundation grant BCS-1551703 to SEB and Binational Science Foundation (BSF-2015606) to AS.